2020
DOI: 10.3390/jcm9061755
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Improvement in Walking Speed on Hospitalization and Mortality in Females with Cardiovascular Disease

Abstract: Cardiovascular disease (CVD) is the principal cause of death in women. Walking speed (WS) is strongly related with mortality and CVD. The rate of all-cause hospitalization or death was assessed in 290 female outpatients with CVD after participation in a cardiac rehabilitation/secondary prevention program (CR/SP) and associated with the WS maintained during a moderate 1 km treadmill-walk. Three-year mortality rates were 57%, 44%, and 29% for the slow (2.1 ± 0.4 km/h), moderate (3.1 ± 0.3 km/h), and fast (4.3 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Effective weight loss, when combined with improved clinical control over CVD risk factors, appears to remain in a strong causative association with the type of medical intervention actually applied [ 35 , 36 ]. These may only consist in specific recommendations regarding weight loss, dietary and/or physical activity interventions, and/or medications prescribed, to be pursued in conjunction with regular monitoring of weight changes [ 37 , 38 , 39 , 40 , 41 ]. In extreme cases, surgical interventions leading to dramatic weight loss are also regarded as a viable option, consequently resulting in significantly improved control over the identified CVD risk factors [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effective weight loss, when combined with improved clinical control over CVD risk factors, appears to remain in a strong causative association with the type of medical intervention actually applied [ 35 , 36 ]. These may only consist in specific recommendations regarding weight loss, dietary and/or physical activity interventions, and/or medications prescribed, to be pursued in conjunction with regular monitoring of weight changes [ 37 , 38 , 39 , 40 , 41 ]. In extreme cases, surgical interventions leading to dramatic weight loss are also regarded as a viable option, consequently resulting in significantly improved control over the identified CVD risk factors [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, significant reduction in cardiovascular disease mortality was observed for participation in swimming, racquet sports and aerobics, but no significant associations were observed for cycling, running and football. Walking is considered a moderate intensity activity, but it can vary according to pace, speed and amplitude ( Yates et al, 2021 ; Grazzi et al, 2020 ). Studies that have investigated the practice of walking in relation to health outcomes have reported significant reductions in the occurrence of diseases and chronic health problems with the practice of walking in populations with or without diagnosis of diseases ( Ikeda et al, 2020 ; Tsuji et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, CVD causes around four million deaths each year, which represents 45% of all deaths [ 2 ]. Considering sex differences, previous studies have shown that women are less likely to experience acute coronary syndromes, but they have a worse evolution following a cardiovascular incident compared to men [ 3 , 4 , 5 ]. The risk of CVD in women is often underestimated due to the misperception that women are more “protected” than men against CVD [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of CVD in women is often underestimated due to the misperception that women are more “protected” than men against CVD [ 6 ]. The clinical manifestations of CVD also differ between men and women [ 3 ]. Among women, CVD tends to appear 7–10 years later than in men and is the main cause of death in women above 65 years of age [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%